2006
DOI: 10.3354/meps317087
|View full text |Cite
|
Sign up to set email alerts
|

Daily movement of the sea urchin Strongylocentrotus droebachiensis in different subtidal habitats in eastern Canada

Abstract: We measured the movement and orientation of sea urchins at 2 sites in each of 4 habitats on urchin barrens in the northern Gulf of St. Lawrence, eastern Canada. We tagged the urchins measuring 25 to 70 mm in test diameter using a non-invasive technique involving a knot of fine monofilament thread tied around one spine. Smaller urchins (< 25 mm) were tagged by tightening a loop around the test. Daily displacement increased markedly going from large juveniles (measuring 10-15 mm in diameter) to small adults (15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 63 publications
3
38
0
1
Order By: Relevance
“…tetracycline and calcein) do not permit individual identification (Hagen 1996, Duggan & Miller 2001, Dumont et al 2006. Laboratory studies have demonstrated the potential of PIT tags in measuring growth and survival, without detectable adverse effects, in 2 species of sea urchin: Strongylocentrotus droebachiensis (Hagen 1996) and Evechinus chloroticus (Woods & James 2005).…”
Section: Introductionmentioning
confidence: 99%
“…tetracycline and calcein) do not permit individual identification (Hagen 1996, Duggan & Miller 2001, Dumont et al 2006. Laboratory studies have demonstrated the potential of PIT tags in measuring growth and survival, without detectable adverse effects, in 2 species of sea urchin: Strongylocentrotus droebachiensis (Hagen 1996) and Evechinus chloroticus (Woods & James 2005).…”
Section: Introductionmentioning
confidence: 99%
“…whereas others find either no effect (Dumont et al, 2006) or the opposite relation (Klinger and Lawrence, 1985). It has also been shown, by using physical models of large algae, that the movement of foliose algae by the water may restrict urchin movement (Konar and Estes, 2003).…”
mentioning
confidence: 99%
“…Both the flow and the chemical signals 32 are likely to be more complex in the urchins' natural environment. In field studies the direction of urchin movement is usually found to be either ran-34 dom or weakly directional (Duggan and Miller, 2001;Dumont et al, 2006;Lauzon-Guay et al, 2006). The question then is how to explain the formation 36 of intense aggregations in an asocial animal, which appears not to be able to move in a directed manner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations